ANALISIS USAHA TAMBAK GARAM DI DESA GEDONGMULYO KECAMATAN LASEM KABUPATEN REMBANG - , RAGIL PUSPITA ANDRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to determinethe cost structure, income, and feasibility of salt farm business at Gedongmulyo Village, Sub District of Lasem, Rembang. The number of salt farmer was 30 owners and they are all selected as respondents (census method). To collect the data, each salt farmer was observed and interviewed, using semiopen questionnaire. The study showed that in average labor cost contributed the highest variable cost reach Rp20,894,631 (84.9%). The highest fixed cost was allocated for land leasing, that amount of Rp8,128,205 (76.28%). Total cost for one hectar of salt farm was Rp35,267,668. Total revenue of the bussines was Rp53,076,281, comprising of Rp41,308,681 (77,83%) from salt poduction and Rp11,767,600(22,17%) for milkfish production. The income of salt farm was Rp17,808,613 per hectar with R/C ratio of 1.50. Therefore the study showed that the bussines was worth to be developed and expanded.